2001
DOI: 10.1046/j.1440-172x.2001.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the FemoStop device and manual pressure in reducing groin puncture site complications following coronary angioplasty and coronary stent placement

Abstract: This study compared two techniques, the FemoStop device (RADI Medical Systems, Uppsala, Sweden) and manual pressure, currently used by nurses to achieve haemostasis at the groin puncture site following removal of femoral arterial sheaths in patients following coronary angioplasty and coronary stent placement. Participants were randomly allocated the FemoStop device or manual pressure. Participants' groins were observed for evidence of complications including haemorrhage, haematoma formation and pseudoaneurysm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 20 publications
1
40
0
Order By: Relevance
“…Bleeding is best controlled by applying pressure until bleeding stops [47][48][49][50][51][52][53] or EMS rescuers arrive (Class I, LOE A). The amount of pressure applied and the time the pressure is held are the most important factors affecting successful control of bleeding.…”
Section: Direct Pressurementioning
confidence: 99%
“…Bleeding is best controlled by applying pressure until bleeding stops [47][48][49][50][51][52][53] or EMS rescuers arrive (Class I, LOE A). The amount of pressure applied and the time the pressure is held are the most important factors affecting successful control of bleeding.…”
Section: Direct Pressurementioning
confidence: 99%
“…The Angio-Seal device is an alternative hemostatic technique that can replace the labor-intensive method of manual compression and may avoid repetitive stress injury. 18 In our study, there were no deployment failures and the complication rate was low. Despite 1 adverse event in group 1, there were no delays in patient discharge.…”
Section: Discussionmentioning
confidence: 45%
“…One LOE 1 randomized, prospective, but not double-blind study, 133 1 LOE 1 metaanalysis, 134 and 5 LOE 2 studies [135][136][137][138][139] showed that hemostasis can be achieved by manual direct pressure over an arteriotomy site after cardiac catheterization. Three LOE 5 animal studies 140 -142 showed that increasing intra-abdominal pressure by insufflation of air can control intra-abdominal bleeding.…”
Section: Consensus On Sciencementioning
confidence: 99%